Preliminary report on the tardigrade diversity of coastal Syowa Station and inland Ser Rondane Mountains, Dronning Maud Land, East Antarctica - Megumu, Tsujimoto; Sandra, J. McInnes; Satoshi, Imura (2013)
第4回極域科学シンポジウム 個別セッション：[OB] 生物圏 11月13日（水）13:00-14:15 国立国語研究所 ２階ラウンジ conference object